B.6 Endovascular treatment of acute ischemic stroke in patients with pre-morbid disability: a meta-analysis. (June 2022) - Bala, F; Beland, B; Mistry, E; Almekhlafi, M; Goyal, M; Ganesh, A
Abstract : Background: Trials of endovascular thrombectomy (EVT) for acute stroke have excluded patients with pre-morbid disability. We performed a meta-analysis to assess the effectiveness and safety of EVT in patients with pre-morbid disability. Methods: According to PRISMA guidelines, we searched for studies describing outcomes in patients with pre-morbid disability (modified Rankin Scale [mRS] 2-5), treated with EVT or medical management (MM). Random-effects meta-analysis was used to pool outcomes including return to baseline mRS at 90 days, symptomatic ICH (sICH), and 90-day mortality. Results: We analyzed 14 studies of patients with pre-morbid disability (mRS2-5: EVT=1, 373, MM=253). Compared to medical therapy, EVT was associated with higher likelihood of return to baseline mRS (OR=2.37, 95%CI:1.39-4.04) and a trend towards lower mortality (OR=0.68, 95%CI:0.46-1.02), with similar odds of sICH (OR 1.01, 95%CI:0.49-2.08). In studies comparing patients with vs. without pre-morbid disability treated with EVT, similar results were found except that pre-morbid disability, when defined more strictly as mRS 3-5, was associated with mortality (OR 3.49, p<0.001). Conclusions: In patients with pre-morbid disability, EVT carries a higher chance of return to baseline mRS compared to patients treated with MM or without pre-morbid disability, although with higher mortality than patients without pre-morbid disability. These findings merit validation with randomized controlled trials.